2023
DOI: 10.3389/fphar.2023.1210393
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-related dysfunction in chronic restraint stress triggers sleep disorders in mice

Abstract: Stress may trigger sleep disorders and are also risk factors for depression. The study explored the melatonin-related mechanisms of stress-associated sleep disorders on a mouse model of chronic stress by exploring the alteration in sleep architecture, melatonin, and related small molecule levels, transcription and expression of melatonin-related genes as well as proteins. Mice undergoing chronic restraint stress modeling for 28 days showed body weight loss and reduced locomotor activity. Sleep fragmentation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The results revealed that mice subjected to Evans-blue-fed restraint stress treatment exhibited anxiety-related behavior, providing evidence of psychological stress’s contribution to this model ( Figure 1 ). These findings are consistent with numerous previous reports that have identified psychological stress as one of the major factors associated with restraint stress animal models [ 6 , 7 , 8 , 16 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Additionally, as psychological-stress-induced immunosuppression is rarely discussed, this model is suitable to address this question.…”
Section: Resultssupporting
confidence: 93%
“…The results revealed that mice subjected to Evans-blue-fed restraint stress treatment exhibited anxiety-related behavior, providing evidence of psychological stress’s contribution to this model ( Figure 1 ). These findings are consistent with numerous previous reports that have identified psychological stress as one of the major factors associated with restraint stress animal models [ 6 , 7 , 8 , 16 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Additionally, as psychological-stress-induced immunosuppression is rarely discussed, this model is suitable to address this question.…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that OFA inhalation may improve the circadian rhythmicity possibly through regulating the HPA axis ( Nicolaides, Charmandari, Chrousos, & Kino, 2014 ). Studies have indicated that chronic restraint stress and disrupted circadian rhythm by light exposure at night are associated with reduced level of melatonin ( Xia et al, 2023 , Emmer et al, 2018 ). Unexpectedly, we found that the concentration of melatonin was not changed by restraint stress and was significantly increased with OFA inhalation and light exposure treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The alteration of melatonin-related pathways was revealed to cause sleep disorders. Tryptophan and 5-hydroxytryptamine levels increased in the hypothalamus, while melatonin levels decreased, as did the transcription and expression of melatonin receptors, and circadian rhythmrelated genes were altered in mice with sleep disorders [49]. 5-hydroxytryptamine functions predominantly to promote wakefulness and to inhibit REM sleep.…”
Section: The Neurochemical Substrates Accompany Aging-related Diseasesmentioning
confidence: 96%